The challenges of financing small and medium scale enterprises (SMEs) in the Ashanti Region -A Case Study of Stanbic Bank (Gh) Ltd - Cofie, Alfred Addotei (2012)
A Thesis submitted to the Institute Of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Commonwealth Executive Masters of Business Administration